Relationship between participation in a transition program and permanence in students at a private university of Lima - Viale-Tudela, Héctor (2024)
Introduction: Will identify the relation generated by participation in a transition program carried out between the end of secondary school and the beginning of higher education with the permanence of first-year students in university. Method: This research is quantitative, longitudinal, non-experimental, with a descriptive and correlational scope. The study is based on a census and the analyzed population is made up of 15710 first-year students from a private Peruvian university. Statistics, such as Chi Square, were used to determine the association or independence of two quantitative variables with a 5% degree of significance. The effect was measured using the V-Cramer statistic. Results: In the seven-year period analyzed there is a statistically significant difference in the student permanence variable in favor of the group of students who attended the transition program. Discussion: These findings confirm that it can be stated that transition programs of academic nature contribute to the permanence of university students